1986
DOI: 10.1016/0035-9203(86)90154-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation increases prevalence and effects of malaria: report on clinical studies in Papua New Guinea

Abstract: A placebo-controlled trial of intramuscular iron dextran prophylaxis for two-month-old infants was carried out on the north coast of Papua New Guinea where there is high transmission of malaria. The results indicate that the placebo group became relatively iron deficient whereas the iron dextran group had adequate iron stores and, in the absence of malaria, a higher mean haemoglobin. However in the iron dextran group there was a higher prevalence of malaria, as judged by parasite and spleen rates at 6- and 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
2
4

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(96 citation statements)
references
References 21 publications
0
90
2
4
Order By: Relevance
“…For instance, the 2-month-old infants included in the later study (Oppenheimer et al, 1986) had probably not developed immunity to malaria, whereas our children had antimalarial antibodies before the iron supplementation. The form of iron supply in the study of Oppenheimer, intramuscular injection of iron, the de®cient nutritional status of their infants, or the high doses of oral iron supplements in other studies (Murray et al, 1978) may also account for the negative effect of iron on infections.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…For instance, the 2-month-old infants included in the later study (Oppenheimer et al, 1986) had probably not developed immunity to malaria, whereas our children had antimalarial antibodies before the iron supplementation. The form of iron supply in the study of Oppenheimer, intramuscular injection of iron, the de®cient nutritional status of their infants, or the high doses of oral iron supplements in other studies (Murray et al, 1978) may also account for the negative effect of iron on infections.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies who concluded a negative impact of iron supplementation on infections (Oppenheimer et al, 1984;Murray et al, 1978), particularly on malaria (Murray et al, 1978;Oppenheimer et al, 1986) are subject to discussion. For instance, the 2-month-old infants included in the later study (Oppenheimer et al, 1986) had probably not developed immunity to malaria, whereas our children had antimalarial antibodies before the iron supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of clinical observations suggest that iron administration may aggravate the risk associated with malarial infection (3)(4)(5). The relative shortage of intracellular hemoglobin in iron-deficient RBC may be responsible for limiting parasite growth (16) .…”
Section: Discussionmentioning
confidence: 99%
“…8 In humans, iron deficiency appears to protect against severe malaria, 9-11 while iron supplementation increases the risks of infection and disease. [12][13][14][15] Iron deficiency also provides protection against infection with Plasmodium berghei in mice. 16,17 M alaria, a major global health challenge worldwide, is accompanied by a severe anemia secondary to hemolysis and increased erythrophagocytosis.…”
Section: Introductionmentioning
confidence: 99%